2016
DOI: 10.1155/2016/7094121
|View full text |Cite
|
Sign up to set email alerts
|

Low-Volume Brachial Plexus Block Providing Surgical Anesthesia for Distal Arm Surgery Comparing Supraclavicular, Infraclavicular, and Axillary Approach: A Randomized Observer Blind Trial

Abstract: Background. Distal arm surgery is widely performed under regional anesthesia with brachial plexus block. The preponderance of evidence for the efficacy relies upon injection of local anesthetic in excess of 30 mL. We aimed to compare three different ultrasound-guided brachial plexus block techniques restricting the total volume to 20 mL. Methods. 120 patients were prospectively randomized to ultrasound-guided brachial plexus block with 20 mL ropivacaine 0.75% at either the supraclavicular, infraclavicular, or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 27 publications
1
24
0
Order By: Relevance
“…In relation to performance time, longer anesthesia-related time was noticed in AXB when compared to SCB, the same was reported by Anatoli et al [3]. Arnuntasupakul et al and Vazin et al also found that SCB resulted in shorter anaesthesia related time which coincides with our results [11,14].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In relation to performance time, longer anesthesia-related time was noticed in AXB when compared to SCB, the same was reported by Anatoli et al [3]. Arnuntasupakul et al and Vazin et al also found that SCB resulted in shorter anaesthesia related time which coincides with our results [11,14].…”
Section: Discussionsupporting
confidence: 92%
“…However, Vazin et al in a study comparing axillary versus supraclavicular block for distal arm surgery concluded that supraclavicular block had a higher success rate than the axillary block [14], which doesn't match the results we reached, and this may be attributed to the multiple injection techniques they used for supraclavicular block while we performed the block through a single injection site.…”
Section: Discussionmentioning
confidence: 60%
“…The success rate with multiple injections is high even with volumes as low as 16e20 ml. 13,14 A single injection technique appears to require greater volumes of injectate: Arcand and colleagues 2 had 80% success rate with 40 ml of LA; Flohr-Madsen and colleagues 15 found MEV50 to be 19 ml with a periarterial injection from 1 to 9 o'clock. Our success rate with 20 ml of dye delivered as a single injection is similar to that reported by Flohr-Madsen and colleagues.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first study that used surface electromyography to quantify the block of individual nerves after an infraclavicular brachial plexus block. Several studies have reported the effect of an infraclavicular brachial plexus block on the axillary nerve using different variations of simple sensory and motor tests, but only as secondary outcomes and results are conflicting, with rates ranging from 9% to 100% .…”
Section: Discussionmentioning
confidence: 99%